Recent advances in pancreatic α-cell transdifferentiation for diabetes therapy - Li, Yanjiao; Zhu, Jinyu; Yue, Congyang; Song, Siyuan; Tian, Limin; Wang, Yi (Frontiers in Immunology, 2025)
As the global prevalence of diabetes mellitus rises, traditional treatments like insulin therapy and oral hypoglycemic agents often fail to achieve optimal glycemic control, leading to severe complications. Recent research has focused on replenishing pancreatic β-cells through the transdifferentiation of α-cells, offering a promising therapeutic avenue. This review explores the molecular mechanisms underlying α-cell to β-cell transdifferentiation, emphasizing key transcription factors such as Dnmt1, Arx, Pdx1, MafA, and Nkx6.1. The potential clinical applications, especially in type 1 and type 2 diabetes characterized by significant β-cell dysfunction, are addressed. Challenges, including low transdifferentiation efficiency, cell stability, and safety concerns, are also included. Future research directions include optimizing molecular pathways, enhancing transdifferentiation efficiency, and ensuring the long-term stability of β-cell identity. Overall, the ability to convert α-cells into β-cells represents a transformative strategy for diabetes treatment, offering hope for more effective and sustainable therapies for patients with severe β-cell loss.